2016
DOI: 10.1038/ncomms11491
|View full text |Cite
|
Sign up to set email alerts
|

An organelle-specific protein landscape identifies novel diseases and molecular mechanisms

Abstract: Cellular organelles provide opportunities to relate biological mechanisms to disease. Here we use affinity proteomics, genetics and cell biology to interrogate cilia: poorly understood organelles, where defects cause genetic diseases. Two hundred and seventeen tagged human ciliary proteins create a final landscape of 1,319 proteins, 4,905 interactions and 52 complexes. Reverse tagging, repetition of purifications and statistical analyses, produce a high-resolution network that reveals organelle-specific intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
219
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 230 publications
(238 citation statements)
references
References 70 publications
9
219
0
1
Order By: Relevance
“…2). This conclusion, based on the analysis of purified Chlamydomonas proteins, was recently confirmed using a "visible immunoprecipitation" (VIP) approach with human proteins (Katoh et al 2016), as well as in human cells in a large-scale proteomic study (Boldt et al 2016). With regard to salt stability, it should be noted that five of the six IFT-B2 proteins are stable at NaCl concentrations of 1 M (Taschner et al 2016), with IFT172 being the only weakly attached subunit, confirming previously published data (Cole et al 1998;Pedersen et al 2005).…”
Section: The Peripheral Ift-b Complex (Ift-b2)supporting
confidence: 67%
See 2 more Smart Citations
“…2). This conclusion, based on the analysis of purified Chlamydomonas proteins, was recently confirmed using a "visible immunoprecipitation" (VIP) approach with human proteins (Katoh et al 2016), as well as in human cells in a large-scale proteomic study (Boldt et al 2016). With regard to salt stability, it should be noted that five of the six IFT-B2 proteins are stable at NaCl concentrations of 1 M (Taschner et al 2016), with IFT172 being the only weakly attached subunit, confirming previously published data (Cole et al 1998;Pedersen et al 2005).…”
Section: The Peripheral Ift-b Complex (Ift-b2)supporting
confidence: 67%
“…A similar destabilization of IFT-B1 (IFT81 and IFT46) and IFT-B2 (IFT57 and IFT20) proteins as well as a slight increase in an IFT-A protein (IFT139) were recently observed in an IFT74 (ift74-2) Chlamydomonas mutant (Brown et al 2015). IFT88 is not required for the stability of the IFT-B1 complex (Pazour et al 2000;Richey and Qin 2012;Taschner et al 2014), but as indicated above is part of the interface between IFT-B1 and IFT-B2 (Boldt et al 2016;Taschner et al 2016). Consistently, the IFT-B complex formed in the ift88 mutant is smaller (Richey and Qin 2012), and IFT57 (IFT-B2 component) but not IFT81 (IFT-B1 component) is destabilized (Pazour et al 2000).…”
Section: Functions Of Ift-b Proteins In Ift-b Complex Formation and Smentioning
confidence: 84%
See 1 more Smart Citation
“…Using our VIP assay, we previously determined the overall architectures of the exocyst, BBSome and IFT-B complexes. The IFT-B complex is composed of 16 subunits that can be divided into the core and peripheral subcomplexes, composed of 10 subunits [IFT22, IFT25 (also known as HSPB11), IFT27, IFT46, IFT52, IFT56, IFT70 (also known as TTC30B), IFT74, IFT81 and IFT88] (Lucker et al, 2005;Taschner et al, 2014) and 6 subunits [IFT20, IFT38 (also known as CLUAP1), IFT54 (also known as TRAF3IP1), IFT57, IFT80 and IFT172], respectively, which are connected to each other by composite interactions involving IFT38, IFT52, IFT57 and IFT88 (Boldt et al, 2016;Katoh et al, 2016;Taschner et al, 2016) (also see Fig. 8).…”
Section: Arl13b Interacts With the Ift-b Complex Via The Ift46-ift56mentioning
confidence: 99%
“…For this, we applied high-resolution affinity proteomics based on tandem affinity purifications (TAPs). We systematically tagged domains of VLGR1 and full-length VLGR1a with the Strep II Flag (SF)-tag ( Figure 1A) and expressed these baits in HEK293T cells for TAPs of protein complexes related to VLGR1 [9,10]. Subsequently, we determined the composition of eluted protein complexes by mass spectrometry.…”
Section: Bodymentioning
confidence: 99%